The Relationship between Extemporaneous Speaking Skills and Academic Performance among Grade 11 HUMSS Students: A Basis for Intervention - Geduriagao, Rizalyn T.; Vibal, Jobell Cris T. (Future Science / FSH-PH Publications, 2025)
This study examined the extent of extemporaneous speaking skills among Grade 11 HUMSS students and analyzed their relationship with academic performance during the 2023–2024 school year. Utilizing a descriptive-correlational research design, the researchers assessed 165 students using standardized rubrics, with evaluations conducted by three communication experts. Academic performance was determined based on the students’ General Weighted Averages. The results indicated that the students demonstrated extemporaneous speaking skills to a great extent and achieved a very satisfactory level of academic performance. A statistically significant relationship was found between the two variables. These results support the need for targeted interventions to enhance students’ speaking abilities, which may, in turn, contribute positively to their academic achievement.